Transformation of Indonesia’s National Health System: A Literature Review on Policy Development and Implementation - Nurmidin, M Fadhel (-, 2025)
The national health system plays a crucial role in ensuring equitable, high-quality, and sustainable healthcare access for all citizens. The reform of Indonesia’s health system continues to evolve, particularly with the introduction of the new Health Law and the optimization of the National Health Insurance (JKN) program. Major challenges include disparities in healthcare access, inefficiencies in the referral system, and the need for a stronger focus on promotive and preventive aspects in primary healthcare services. This study employs a qualitative method using policy analysis and literature review approaches. Data sources include policy documents, research reports, and scholarly publications discussing the transformation of the national health system. The analysis examines the effectiveness of implemented policies, challenges in execution, and the potential for strengthening the health system through digitalization and service innovation. Findings indicate that the digitalization of healthcare services, such as the implementation of electronic medical records and technology-based referral systems, has improved efficiency and accessibility. However, challenges remain in system integration, digital infrastructure gaps, and the readiness of healthcare professionals. Additionally, while promotive and preventive approaches are gaining greater attention in reducing the morbidity of non-communicable diseases, implementation at the primary healthcare level remains suboptimal. This study concludes that the success of the national health system depends on the synergy between policy, technology, and the capacity-building of healthcare professionals. Effective digital system integration and the strengthening of promotive and preventive primary healthcare services are key to achieving a more inclusive, efficient, and sustainable health system.